The Effect of maltodextrin concentration and temperature process on physicochemical characteristics of instant lemon (Citrus limon l) powder minute using crystallization machine - TRIYONO, Agus; HARIADI, Hari; ANGGARA, Cahya Edi Wahyu; SUSANTI, Novita Dwi; NUGROHO, Pramono; HANIFAH, Umi; NOVIANTI, Fithria; KUALA, Seri Intan; PURWANDOKO, Pradeka Brylian; MAYASTI, Nur Kartika Indah; HARYANTO, Aidil; RAHMAN, Nurhaidar; et al. (Food Science and Technology, 2024)
The purpose of this study was to determine the effect of maltodextrin concentration and drying temperature on the physicochemical characteristics of instant lemon powder drinks. The research used the randomized design group with a 3x3 factorial pattern consisting of two factors with two repeats so that 18 experimental units were obtained. There is a T factor which is a concentration of maltodextrin consisting of three levels, namely t1 (10%), t2 (15%), and t3 (20%), and a K factor that is a variation of the process temperature also consisting of three levels, namely k1 (50°C), k2 (60°C), and k3 (70°C). In this study, physical responses include solubility, dissolving time, amount of yield, hygroscopicity, bulk density, and scanning electron microscopy. Chemical responses correspond to water content, antioxidant activity, pH value, and vitamin C. The results showed that maltodextrin concentration can affect solubility, dissolving time, amount of yield, hygroscopicity, bulk density, water content, pH value, and vitamin C. Variations in process temperature affect solubility, dissolving time, amount of yield, hygroscopicity, bulk density, moisture content, pH value, and vitamin C. The interaction of maltodextrin concentration and process temperature variations affects hygroscopicity but not solubility response, dissolving time, yield amount, bulk density, water content, pH value, and vitamin C.